Evaluation of the activity of arginase and some biochemical parameters in sera of patients with acromegaly (Baghdad Science Journal, 2024)
The objective of the present study was to study the effect of increasing Growth Hormone (GH) on arginase activity in sera of Iraqi acromegaly (ACRO) patients. Certain Vital biochemical parameters were measured such as Growth Hormone (GH), Insulin-Like Growth Factor-1 (IGF-1), Fasting Serum glucose (FSG), Urea, Total Cholesterol (TC), Triglycerides (TG), High-density lipoprotein-cholesterol (HDL-C), Low-density lipoprotein-cholesterol (LDL-C), and very low-density lipoprotein-cholesterol (VLDL-C). Eighty people between the ages ranged between of 25 and 65 were involved in this study, 40 of them were ACRO Iraqi patients and the remaining 40 were healthy controls. All participants were matched in age and sex and the body mass index (BMI) were calculated for each group. Arginase activity was reduced in ACRO patients significantly (p<0.05) compared to controls, also the HDL-C levels were reduced significantly p<0.05, while the levels of GH, IGF-1, TC, TG, LDL-C, and VLDL-C were elevated significantly p<0.05. There were no significant differences in the levels of FSG and urea between the patients and controls p>0.05. Results of the present study have revealed that patients with ACRO have significantly lower levels of serum arginase activity and not significantly lower levels of serum urea, which means their bodies retain more nitrogen compounds for use in building processes.